Maximal lactate steady state in running mice: Effect of exercise training - Ferreira, Julio C. B.; Rolim, Natale P. L.; Bartholomeu, Jan B.; Gobatto, Claudio A.; Kokubun, Eduardo [UNESP]; Brum, Patricia C. (Blackwell Publishing, 2007)
1. Maximal lactate steady state (MLSS) corresponds to the highest blood lactate concentration (MLSSc) and workload (MLSSw) that can be maintained over time without continual blood lactate accumulation and is considered an important marker of endurance exercise capacity. The present study was undertaken to determine MLSSw and MLSSc in running mice. In addition, we provide an exercise training protocol for mice based on MLSSw.2. Maximal lactate steady state was determined by blood sampling during multiple sessions of constant-load exercise varying from 9 to 21 m/min in adult male C57BL/6J mice. The constant-load test lasted at least 21 min. The blood lactate concentration was analysed at rest and then at 7 min intervals during exercise.3. The MLSSw was found to be 15.1 +/- 0.7 m/min and corresponded to 60 +/- 2% of maximal speed achieved during the incremental exercise testing. Intra- and interobserver variability of MLSSc showed reproducible findings. Exercise training was performed at MLSSw over a period of 8 weeks for 1 h/day and 5 days/week. Exercise training led to resting bradycardia (21%) and increased running performance (28%). of interest, the MLSSw of trained mice was significantly higher than that in sedentary littermates (19.0 +/- 0.5 vs 14.2 +/- 0.5 m/min; P = 0.05), whereas MLSSc remained unchanged (3.0 mmol/L).4. Altogether, we provide a valid and reliable protocol to improve endurance exercise capacity in mice performed at highest workload with predominant aerobic metabolism based on MLSS assessment.
Keywords: blood lactate; endurance capacity; exercise training; mice